LiSER: a software experience management tool to support organisational learning in software development organisations - Mohamed, A.; Lee, S.P.; Salim, S.S. (2005)
Abstract: The efficient management of experience knowledge is vital in todays knowledge-based economy. This paper is concerned with developing a software experience management tool as an organisational memory subsystem. The tool aims to support Knowledge Management (KM) and Organisational Learning (OL) activities in a typical software organisation. It is specifically targeted to capture the pearls of tacit knowledge in the form of Knowledge Asset (K-Asset), which only surface as the outcome of collaborative analysis and refinement of the captured knowledge. The prototype tool is based on the framework for collaborative organisational learning we developed in previous research.